Islamic Banking Literature Review. Is Islamic Banking in Accordance with Sharia Principles? - Harsono, Mugi; Atina, Vivin Zulfa (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2023)
The purpose of this study is to explore the meaning and issues of Islamic banking between 2012 and 2022. Data acquisition based on Scopus and Google Scholar databases using systematic literature reviews (SLR). We identified the need for SLR in Islamic Banking publications. The purpose of this study is to overcome differences in viewpoints in the context of Islamic banking to provide a clear classification view of the resulting research articles. This article highlights the current collaboration between the authors, to identify gaps in the review of Islamic banking literature. This research is a descriptive qualitative research by explaining the meaning and issues of previous research based on the similarity of titles and related differences to find results that are more relevant to the current condition of Islamic banking. The result of the study found that researchers generally define Islamic banks as banks based on sharia principles that promote mutual prosperity and optimal social achievement.